Identification and implication of an allergenic PR‐10 protein from walnut in birch pollen associated walnut allergy. Issue 4 (10th February 2017) - Wangorsch, Andrea; Jamin, Annette; Lidholm, Jonas; Gräni, Nora; Lang, Claudia; Ballmer‐Weber, Barbara; Vieths, Stefan; Scheurer, Stephan
Abstract : In walnut extract, a Bet v 1‐like, PR–10 protein (Jug r 5) was identified. Due to high 3D homology of the two proteins, birch pollen allergic patients with concomitant walnut allergy display IgE cross‐reactivity with Jug r 5. Diagnostic use of Jug r 5 will compensate for the low sensitivity of walnut extract for patients with birch pollen associated walnut allergy. Abstract : Scope: English walnut ( Juglans regia ) belongs to the most important allergenic tree nuts. Co‐sensitization with birch ( Betula verrucosa ) pollen has been reported. We aimed to identify a walnut allergen homologous to the major birch pollen allergen Bet v 1. Methods and results: A cDNA encoding a Bet v 1‐homologous allergen (Jug r 5) in walnut kernels was cloned by RT‐PCR. Jug r 5 was expressed in Escherichia coli, purified by column chromatography and characterized by circular dichroism spectroscopy. Specific IgE levels to walnut, Bet v 1, and Jug r 5 in birch pollen allergics ( n = 16) with concomitant walnut allergy were measured by ImmunoCAP: 44% of the patients were tested positive to walnut while 94% were reactive to Jug r 5, and 100% to Bet v 1. Jug r 5 and Bet v 1 allergens showed bidirectional IgE cross‐reactivity by competitive ELISA and were capable of inducing histamine release from effector cells. Immunoblot competition experiments demonstrated the presence of IgE‐reactive Jug r 5 in walnut extract, but at low levels. Conclusion: A Bet v 1‐like allergen was identified in walnut. Diagnostic use of Jug r 5 will compensate for the low sensitivity of walnut extract for patients with birch pollen associated walnut allergy.